The Influence of Irrigation Regimes on the Yield and Fruit Quality of Date Palm Trees - Khalid Almutairi; Hussien Al dalwi; Lidia Sas-Paszt; Walid Mosa (BioResources)
One of the big problems in Saudia Arabia is the scarcity of irrigation water, and this extremely affects the yield of plant components. Consequently, determination of the best water irrigation requirements for the growth and productivity of date palm trees is needed. The current study was performed on three date palm cultivars: ‘Khalas’, ‘Nabbut’, and ‘Rothana’ to investigate the effect of 100% (19.2 m3), 80% (15.36 m3), 60% (11.52 m3), and 40% (7.68 m3) irrigation on the yield and fruit quality characteristics. The results showed that irrigation with 100% and 80% significantly increased the fruit yield, marketable fruit number, and fruit weight. Moreover, these regimes also greatly increased the fruit content from total and reduced sugars, and soluble solids compared with 40% and 60% regimes. The 100% and 80% irrigation regimes reduced the fruit acidity but the differences between 100%, 80%, 60%, and 40% water irrigation were not significant in ‘Khalas’ or ‘Nabbut’. The effect of 100% was significant compared with the influence of 40%. The water footprint was significantly higher with 100% and 80% rather than with 60% or 40%.